Study of The Compliance Level of Students at The Krabi Thai Islamic Boarding School In The Implementation Of Character-Based Discipline - Nor Mita Ika Saputri; Husniah Ramadhani Pulungan; Muhammad Darwis; Marlina Harahap; Darliana Sormin; Nor Kalsum Mohd Isa; Mr. Nopparat Sumalee (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The application of discipline is a character strengthening that produces knowledgeable and noble graduates. This study used descriptive qualitative method. The selected informants were teachers from three schools which consisted of the Santitham Muslim Foundation School, the Vuttisat Pittayanusorn School, and the Adameesuksavittaya School. Data collection techniques using a questionnaire. Then, data reduction, data classification, data presentation, and drawing conclusions are data analysis techniques. Adameesuksavittaya school appears to excel in dress discipline as evidenced by three statements each at 13% and discipline in worship as evidenced by five statements each at 11%. Then, the Santitham Muslim Foundation School looks superior in student obedience in time discipline as evidenced by two statements of 16% each. Meanwhile, the Vuttisat Pittayanusorn School appears to have excelled in student compliance in discipline as evidenced by three statements of 14% each. Thus, the novelty of the level of student discipline compliance can reveal the characteristics of school education in showing its good image to the community. This research resulted in a statement that the tendency of students to obey the rules in their schools can be reflected in their daily behavior.